2023
DOI: 10.1002/fsn3.3284
|View full text |Cite
|
Sign up to set email alerts
|

Changes in fatty acids during storage of artisanal‐processed freshwater sardines (Rastrineobola argentea)

Abstract: For ages, indigenous small fish species have been important in food and nutritional security of poor communities in low income countries. Freshwater fish, in particular fatty fish species are attracting a great attention because they are good sources of health promoting long chain omega‐3 fatty acids. Docosahexaenoic acid (DHA, C22:6n‐3), Docosapentaenoic acid (DPA, C22:5n‐3) and eicosapentaenoic acid (EPA, C20:5n‐3) are the main omega‐3 PUFAs known to confer health benefits in humans if consumed in required a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
(49 reference statements)
1
4
0
Order By: Relevance
“…Interestingly, the SFA of both C. vulgaris and T. chui also showed a decrease under light, frozen, and heated conditions compared to the control condition. This reduction was already observed in other food matrices during storage [ 31 ]. The decrease in SFA as well as other FA could potentially be linked to the action of lipases.…”
Section: Discussionsupporting
confidence: 73%
“…Interestingly, the SFA of both C. vulgaris and T. chui also showed a decrease under light, frozen, and heated conditions compared to the control condition. This reduction was already observed in other food matrices during storage [ 31 ]. The decrease in SFA as well as other FA could potentially be linked to the action of lipases.…”
Section: Discussionsupporting
confidence: 73%
“…These results support the use of OV50 as a biopreservative in fresh sardines. Proteins have a major impact on the texture and nutritional value of sardines [32], while lipids are capable of causing rancidity and degrading the flavor of foods [33]. Maintaining these natural protein and lipid levels throughout product storage is expected to be an added value, which was ensured by the OV50 strain used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, palmitic acid has been associated with increased low-density lipoprotein cholesterol, which could increase the risk of developing cardiovascular disease (CVD) in humans [38]. Previous studies have shown that palmitic acid is the most abundant saturated fatty acid, which decreases with increasing storage time [40]. Te C4, MA, and LV groups had the lowest palmitic acid relative content among the treatment groups.…”
Section: Fatty Acid Analysismentioning
confidence: 99%